High-Resolution CT of Interstitial Lung Disease: A Continuous Evolution - Walsh, Simon L. F.; Hansell, David M. (Seminars in Respiratory and Critical Care Medicine, 2014)
Before the advent of high-resolution computed tomography (HRCT), the role of imaging, chest radiography in particular, in the management of patients with interstitial lung disease was limited. In the past 25 years, this has radically changed. HRCT has transformed the diagnostic landscape by providing detailed cross-sectional imaging of the lungs, which permit ready identification of a variety of different interstitial lung diseases. Although the position of HRCT as the dominant imaging technique for interstitial lung disease has remained unchallenged since its introduction in the late 1980s, the roles assumed by HRCT have undergone a steady evolution. This evolution has occurred in stages. The first investigations of HRCT in interstitial lung disease during the late 1980s and early 1990s marked a golden era of HRCT-pathologic correlative studies, typified by the work of Müller and Miller. It was this groundbreaking work that defined basic HRCT patterns, correlated to histopathologic appearances, which underpin the pattern recognition approach used to interpret HRCT images to this day. Subsequently, attention turned to issues of disease reversibility and responsiveness and how this could be predicted by HRCT. At the turn of the millennium, the previously long accepted belief in histopathological diagnosis as the reference standard in interstitial lung disease gave way to a growing perception that histopathology was not infallible. This change in diagnostic thinking arguably has had the biggest impact on how HRCT's role subsequently evolved. Recently, HRCT data have been integrated with pulmonary function in staging models to predict prognosis particularly in idiopathic fibrosing lung disease. This article reviews these stages of evolution. The emergence of the multidisciplinary approach to diagnosis will also be considered.
Keywords: HRCT; interstitial lung disease; CT-pathological correlative studies; prognostication; staging